The impact of job satisfaction on the effective motivation of the personnel (Путеводитель предпринимателя, 2020)
The paper shows the importance of job satisfaction as the motivational state of the inherent to any worker and its impact on the effective motivation of the personnel. Classification is given of motivational States of the person. Given the author’s interpretations of concepts — satisfaction with work and labour motivational state.